Os lugares em que vivemos: múltiplos olhares sobre as paisagens e culturas brasileiras a partir do cinema - Veríssimo e Silva, Luiz Gustavo (Universidade Federal de São Carlos, 2025)
This study analyzes the use of Brazilian national cinema as a didactic resource in Geography teaching, aiming to explore how short films can contribute to understanding the different ways of inhabiting Brazilian landscapes. The research, qualitative in nature, was carried out with 4th-grade elementary school students in a municipal school in the interior of Minas Gerais. The pedagogical approach included the screening of the short films Naiá and the Moon, Waters of Romanza, and The Things That Live in Things, followed by discussion circles and the production of drawings. The analysis of the graphic records, in light of Peircean semiotics, made it possible to identify conceptual, procedural, and attitudinal learning related to cultural diversity, the human-nature relationship, and the forms of organization of geographic space. The results indicate that national cinema, by integrating artistic language with curricular content, fosters the construction of more sensitive, critical, and reality-connected geographic knowledge
The places we live: multiple perspectives on Brazilian landscapes and cultures through cinema
Keywords: Educação estética; Geografia humanista; Linguagem cinematográfica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM